A high potency multi‐strain probiotic improves glycemic control in children with new‐onset type 1 diabetes mellitus: A randomized, double‐blind, and placebo‐controlled pilot study. Issue 7 (3rd July 2021) - Kumar, Sanjeev; Kumar, Rakesh; Rohilla, Latika; Jacob, Neenu; Yadav, Jaivinder; Sachdeva, Naresh
Abstract: Background: Studies in animal models and humans with type 1 diabetes mellitus (T1DM) have shown that probiotic supplementation leads to decreased pro‐inflammatory cytokines (responsible for damaging β‐cells of the pancreas), improved gut barrier function, and induction of immune tolerance. Objective: To study the effect of supplementation of probiotics in children with T1DM on glycemic control, insulin dose, and plasma C‐peptide levels. Methods: A single‐centered, double‐blinded, and randomized placebo‐controlled pilot trial was conducted in children (2–12 years) with new‐onset T1DM. Ninety‐six children were randomized and allocated to Placebo or Intervention groups. The intervention included high dose (112.5 billion viable lyophilized bacteria per capsule) multi‐strain probiotic De Simone formulation (manufactured by Danisco‐Dupont) sold as Visbiome® in India. The probiotic was supplemented for 3 months and HbA1c, fasting C‐peptide, blood sugar records, and insulin dose was recorded at baseline and 3 months. Results: A total of 90 patients (45 in each group) were analyzed for outcome parameters. We found a significant decrease in HbA1c (5.1 vs. 3.8; p  = 0.021) and a significant decline in total and bolus insulin dose (U/kg/day; p  = 0.037 and 0.018, respectively) in the intervention group when compared with the placebo group. A significantly higher ( p  = 0.023) number of children achieved remission in the treatment group. We did not notice adverse effects in either of the study groups. Conclusion: Children with newly diagnosed T1DM managed with standard treatment along with probiotics showed better glycemic control and a decrease in insulin requirements; however, more extensive studies are further warranted.